2020
DOI: 10.2147/ott.s263637
|View full text |Cite
|
Sign up to set email alerts
|

<p>SNHG3 Knockdown Suppresses Proliferation, Migration and Invasion, and Promotes Apoptosis in Non-Small Cell Lung Cancer Through Regulating miR-216a/ZEB1 Axis</p>

Abstract: Background Tumour growth and development are dependent on many factors including long noncoding RNAs (lncRNAs). However, limited information is available on the involvement of lncRNAs in non-small cell lung cancer (NSCLC) and the molecular mechanisms have not been defined. Here, we examined the expression of small nucleolar RNA host gene 3 (SNHG3) and its contribution to the development of NSCLC. Methods We detected SNHG3, miR-216a, and ZEB1 expression in tissues from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…On the contrary, the patients with positive expression of E-cad had a more favorable OS time when compared with patient who did not express E-cad. The above results were consistent with the previous other studies [16,18,19]. Aberrant expression of ZEB1 and E-cad should be thought useful and valuable biomarkers for prediction of IUCB patients' prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, the patients with positive expression of E-cad had a more favorable OS time when compared with patient who did not express E-cad. The above results were consistent with the previous other studies [16,18,19]. Aberrant expression of ZEB1 and E-cad should be thought useful and valuable biomarkers for prediction of IUCB patients' prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have also found that SNHG3 promotes the proliferation and metastasis of non-small cell lung cancer cells by competing with other miRNAs (miR-340-5p and miR-216a-5p). 26 , 27 These data also confirm the important regulation of SNHG3 in non-small cell lung cancer cells, and the SNHG3/miR-515-5p/SUMO2 we found may be only the tip of the iceberg of SNHG3 regulatory network.…”
Section: Discussionsupporting
confidence: 79%
“…For example, SNHG3 promoted hepatocellular tumorigenesis by regulating miR-326 expression [ 21 ], and SNHG3 modulated the miR-384/WEE1 G 2 checkpoint kinase axis to regulate laryngeal carcinoma cell proliferation and migration [ 22 ]. In addition, the lncRNA SNHG3 was reported to play a vital role in LUAD progression [ 23 , 24 ]. However, to the best of our knowledge, the tumorigenic properties and underlying mechanism of action of SNHG3 in LUAD progression remain to the determined.…”
Section: Discussionmentioning
confidence: 99%